Implementation of Facebook Marketplace for Convection and Embroidery UMKM Products (Jack Convection Medan) as an Effort to Increase Online Marketing and Sales - Aisyah, Siti; Hutasuhut, Muhammad Anshari (BIMA Journal (Business, Management, & Accounting Journal), 2023)
This research is entitled Implementation of Facebook Marketplace for Convection and Embroidery UMKM Products (Jack Convection Medan) as an Effort to Increase Online Marketing and Sales. The purpose of this research is to promote library services at the Muhammadiyah University of North Sumatra. The aim of the research is to find out that social media (Facebook) can provide convenience for MSME actors, especially for convection and embroidery business people. This study uses a descriptive qualitative research method. Marketing and sales of MSME products are currently carried out by participating in various MSME product exhibitions organized by the government and business actors who provide exhibition facilities, broadcast messages, and wait for customers to arrive at the store. This way of disseminating information is not effective because it does not reach people who live far from museums or retail locations that hold exhibitions. Facebook has a marketplace feature that allows promotions and sales to be unlimited by space and time, making it one of the social media platforms that is currently widely used and in demand by MSME players. By utilizing the Facebook marketplace, MSME can more easily market their products and make sales via smartphones, which will help them increase their sales growth. The results of this research are expected to be input for MSME actors who are pioneering or who are already successful, namely how to promote their products via Facebook in this modern era so that their products are widely accessible to many people. .